An Assessment of the Priorities and Efficiency of Pakistan's Public Sector Educational Expenditure (The Pakistan Development Review, 1984)
Expenditure on education is very often justified on the grounds that it is the means of providing equality of opportunity. Actually, at least two related factors prevent each child from getting an equal chance to flourish academically. Firstly, in a dual system of education, elite private schools coexist with the often substandard government schools (urban and rural) and private schools. Entrance into the elite private schools is based on influence or wealth. The recipients of this schooling are prepared for better careers, with acquired ability and contacts paving the way.